Screening for symptoms of childhood traumatic stress in the primary care pediatric clinic - Kristine A. Campbell; Kara A. Byrne; Brian L. Thorn; Lindsay Shepard Abdulahad; R. Neal Davis; Lisa L. Giles; Brooks R. Keeshin (BMC, 2024)
Abstract Background Childhood traumatic experiences may result in post-traumatic stress disorder. Although pediatricians are encouraged to address these traumas in clinical encounters, measures of childhood traumatic stress have not been adopted by primary care clinicians. In this study, we describe the feasibility and potential utility of the UCLA Brief Screen, a validated screener for childhood traumatic stress symptoms, in pediatric primary care clinics. Methods Children 6-17 years of age presenting for routine well-child care in community-based pediatric clinics were eligible for traumatic stress screening. We described the feasibility and acceptability of screening based on screener adoption by eligible pediatric clinicians. We assessed the potential utility of screening based on prevalence and distribution of potentially traumatic events and traumatic stress symptoms in this general pediatric population. Finally, we compared results of the UCLA Brief Screen with those of the Patient Health Questionnaire-A to evaluate associations between symptoms of traumatic stress, depression, and suicidality among adolescents in this community setting. Results 14/18 (77.8%) pediatric clinicians in two clinics offered an adapted UCLA Brief Screen during 2359/4959 (47.6%) eligible well-child checks over 14 months. 1472/2359 (62.4%) of offered screeners were completed, returned, and scored. One-third (32.5%) of completed screeners captured a potentially traumatic event experience described by either children or caregivers. Moderate to severe traumatic stress symptoms were identified in 10.7% and 5.2% of patients, respectively. Concurrent depression screening revealed that 68.3% of adolescents with depressive symptoms reported a potentially traumatic event (PTE) and 80.5% had concurrent traumatic stress symptoms. Adolescents reporting a PTE were 3.5 times more likely to report thoughts of suicide or self-harm than those without this history. Conclusions Results from this pilot study suggest that traumatic stress screening in the pediatric primary care setting may be feasible and may identify and classify mental health symptoms missed with current screening practices for depression. The prevalence of PTEs and traumatic stress symptoms associated with PTEs support the potential utility of a standardized screening in early identification of and response to children with clinically important symptoms of childhood traumatic stress. Future research should evaluate meaningful clinical outcomes associated with traumatic stress screening.